2022
DOI: 10.3390/ijms23031912
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial-Targeted Therapy for Doxorubicin-Induced Cardiotoxicity

Abstract: Anthracyclines, such as doxorubicin, are effective chemotherapeutic agents for the treatment of cancer, but their clinical use is associated with severe and potentially life-threatening cardiotoxicity. Despite decades of research, treatment options remain limited. The mitochondria is commonly considered to be the main target of doxorubicin and mitochondrial dysfunction is the hallmark of doxorubicin-induced cardiotoxicity. Here, we review the pathogenic mechanisms of doxorubicin-induced cardiotoxicity and pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(49 citation statements)
references
References 217 publications
(263 reference statements)
0
48
0
1
Order By: Relevance
“…Several mechanisms may be responsible for doxorubicin-induced cardiotoxicity. These mechanisms include mitochondrial injury, ROS generation, intracellular Ca+2 dysregulation, inflammatory cytokine production, and myocyte damage ( Rawat et al, 2021 ; Sheibani et al, 2022 ; Wu et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms may be responsible for doxorubicin-induced cardiotoxicity. These mechanisms include mitochondrial injury, ROS generation, intracellular Ca+2 dysregulation, inflammatory cytokine production, and myocyte damage ( Rawat et al, 2021 ; Sheibani et al, 2022 ; Wu et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…DOX treatment in patients shows both effects like therapeutic and toxic effects. It has been reported that the cardiomyopathy initiated by doxorubicin is a progressive and multifactorial process (Wu et al, 2022), including oxidative stress, iron accumulation with the alteration of gene and protein expression and DNA breakage via inhibition of topoisomerase II (Kong et al, 2022).…”
Section: Advances Inmentioning
confidence: 99%
“…As there are both hydrophobic and hydrophilic domains in the molecular structure, DOX is characteristic of a phospholipid-loving molecule, which is, therefore, the most susceptible target organ. Studies have pointed out that DOX can not only disturb the normal transmission of the respiratory chain and the structure and function of creatine kinase in mitochondria but also that the concentration of DOX in mitochondria is 100 times that in plasma; induced bioenergy disorder is one of the markers of cardiotoxicity caused by DOX [ 12 , 13 ]. As we all know, normal energy supply is a necessary condition to ensure the normal physiological and biochemical process of myocardial cells and the material basis to maintain the stability of the internal environment of the heart and the diastolic and contractile functions of the heart [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%